Teaching of English Writing Skills at Secondary level in Muslim Countries: A Comparative Study of Public and Private Schools in District Muzaffargarh, Pakistan (Al-Qamar, 2022)
This research paper expounds the concept, legitimacy and standards of the notion of wakalah in pre-modern Islamic jurisprudence and examines its practices in the contemporary Islamic finance industry. Wakalah plays an important role in the current financial institutions as almost all the contracts of Islamic banking and finance are revolving around wakalah such as Murabaha, Mudharabah, Diminishing Musharakah, Ijarah, Salam, Istisna, and Tawarruq Financing etc.  It can be claimed that the current Islamic banks cannot fulfil their daily activities without the involvement of wakalah. However, on the other hand, it is presumed by many that the contemporary practices of wakalah does not fulfill the requirements of the notion of wakalah enunciated in the classical Islamic jurisprudence because sometimes, the transactions seem like mere subterfuges and stratagems (hiyal) to circumvent the prohibitions prescribed by Shariah, hence, there’s an immense need to critically evaluate these practices in the light of well-established principles. This paper is aimed to fill this research gap in the existing literature on the subject of wakalah. The paper is based on the qualitative research methodology i.e. descriptive, analytical and critical. The paper is concluded with concrete recommendations for further improvement in the practices of wakalah in current Islamic financial institutions to meet the requirements of Shariah.
Keywords: English; Teaching; Skills; School; Secondary Level